Electrochemical study of Trametes Versicolor laccase compatibility to different polyphenolic substrates - Sýs, Milan; Metelka, Radovan; Frangu, Arber; Vytřas, Karel; Arbneshi, Tahir (My University, 2017)
The aim of this electrochemical study was to ascertain which position of hydroxy groups on a benzene ring provides electroactive products after enzymatic oxidation by laccase originating from the Trametes versicolor mushroom, exhibiting intense redox signals that are exploitable for their amperometric determination. The electrochemical properties of phenol together with all isomers of benzenediol and cresol at the bare carbon paste electrode (CPE) and CPE modified with enzyme laccase (CPE/Laccase) were investigated using cyclic voltammetry at various scan rates. Comparison of resulting redox signals and their differences confirmed the suitability of classes of polyphenolic compounds as substrates for Trametes versicolor laccase and their potential use as suitable biological components in the development of amperometric enzyme biosensors for the determination of such species. The feasibility of the proposed approach was verified by electrochemical assays of the enzymatic oxidation of polyphenolic analogues of simple phenols, e.g., gentisic acid, caffeic acid, resveratrol, and others.
Elektrochemická studie kompability lakázy z Tramates Versicolor k různým polyfenolickým látkám
Keywords: Carbon paste electrode; laccase; phenol; benzenediols; cresols; cyclic voltammetry; Uhlíková pastová elektroda; lakáza; fenol; benzodioly; krezoly; cyklická voltametrie